Does government-backed lending prevent unemployment? An assessment of the Swiss COVID-19 lending program - Daniel Kaufmann (University of Neuchâtel, Institute of Economic Research (IRENE), 2020)
This paper identifies the effect of variation in government-backed loan supply on unemployment exploiting regional variation in the Swiss COVID-19 lending program. The rules of the program introduce variation in loan supply across Cantons. This variation helps disentangling supply from demand effects. Higher loan supply reduces unemployment. Increasing the volume by CHF 100,000 saves between 0.22 and 0.29 jobs. Therefore, loan supply has to expand by between CHF 344,800 and CHF 454,500 to save one job. Taking into account that some of the borrowers default, saving one job costs the government between CHF 39,700 and CHF 52,400 per year. These costs are somewhat lower than unemployment benefits associated with the median income.
Keywords: E24; E32; E44; E58; E62; E61; G21; G23; G28; H12; R12; 330; Government-backed lending; targeted lending; unemployment; COVID-19